ANALYSIS OF CONSUMER BEHAVIOR IN IMPROVING PRODUCT PURCHASE DECISIONS AT UD. NIAS BERSAMA - Ya’aro Hulu; Nov Elhan Gea; Yupiter Mendrofa; Maria Magdalena Bate’e (LPPM YPITI, 2026)
This study aims to determine how the impact of consumer behavior increases product purchasing decisions at UD. Nias Bersama. The research method used in this study uses qualitative research methods. Collection techniques consist of interviews, observations, and documentation. The results of the study indicate that. Based on the results of the study, consumer behavior has been shown to play an important role in driving purchasing decisions through trust in products, positive emotional experiences, and the attractiveness of prices and promotions, although there are still obstacles in the form of relatively high prices compared to competitors and inconsistent product availability. To overcome these obstacles, UD. Nias Bersama implements a holistic strategy by setting competitive prices, managing product stocks reliably, improving service quality, differentiating, and implementing relevant and targeted promotions. This effort is in line with the concept of value creation and customer satisfaction in modern marketing theory so as to strengthen consumer purchasing decisions.